The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1073/pnas.1905966116
|View full text |Cite|
|
Sign up to set email alerts
|

Regenerative and durable small-diameter graft as an arterial conduit

Abstract: Despite significant research efforts, clinical practice for arterial bypass surgery has been stagnant, and engineered grafts continue to face postimplantation challenges. Here, we describe the development and application of a durable small-diameter vascular graft with tailored regenerative capacity. We fabricated small-diameter vascular grafts by electrospinning fibrin tubes and poly(e-caprolactone) fibrous sheaths, which improved suture retention strength and enabled long-term survival. Using surface topograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 86 publications
1
30
0
3
Order By: Relevance
“…Recent advances in tissue‐engineered blood vessels have enabled the modeling and improved understanding of complex biological phenomena. [ 14,15 ] Specifically, various methods to recreate critical components of the muscular remodeling have been developed to systematically study the cellular events and interactions involved in VPCs. Incorporating chemokines promoting stem cells recruitment in polymeric grafts and young cells engineered extracellular matrices have proven capable in promoting VPCs homing and myogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in tissue‐engineered blood vessels have enabled the modeling and improved understanding of complex biological phenomena. [ 14,15 ] Specifically, various methods to recreate critical components of the muscular remodeling have been developed to systematically study the cellular events and interactions involved in VPCs. Incorporating chemokines promoting stem cells recruitment in polymeric grafts and young cells engineered extracellular matrices have proven capable in promoting VPCs homing and myogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding positive development of the HUV as vascular graft, the flow conditioning impacted the bulk mechanics of both CF and PMPD constructs, with burst values that significantly increased over the remodeling process going from approximately 600 mmHg for the decellularized scaffolds to approximately 890–986 mmHg for the recellularized constructs at Day 55 (6 weeks of culture). These burst pressure values remain lower than those of native tissues (human saphenous vein: 1,680–2,273 mmHg (Elliott et al, 2019; L'Heureux et al, 2006) and human artery: 2,031–4,225 mmHg (Elliott et al, 2019; L'Heureux et al, 2006)) and of vessels developed by other research groups, such as the rolled vessels developed by L'Heureux et al (>3,000 mmHg) (L'Heureux et al, 2006). However, the burst pressures obtained are superior to the pressure levels encountered in the physiological environment (normally <200 mmHg) and increased throughout the conditioning process to reach high values for a vascular graft developed in vitro based on an acellular human scaffold after a 55 days culture period, indicating the promising remodeling of the scaffold based on a vein toward an artery.…”
Section: Discussionmentioning
confidence: 94%
“…M2 macrophages have been related to the tissue remodeling process, avoiding the activation of T and B cells [ 265 ]. Moreover, several research groups have observed the development of vasa vasorum, the responsible vessels for nutrient supplementation, into the transplanted vascular grafts, indicating its further proper adaptation by the studied living system [ 172 , 266 ].…”
Section: Discussionmentioning
confidence: 99%